The impact of opportunity sales (discounts) on Impulse purchase for clothes in the Saudi society and measuring the community's awareness of the negative repercussions of Impulse purchase on the environment - Al-Ahmari, Ihsan Ayed; Al-Dabbagh, Maha Abdullah (Journal of Humanities & Social Sciences, 2023)
This study examines the influence of opportunistic sales on compulsive clothing purchases in Saudi society, with a particular focus on women in Jeddah. The rise of e-commerce and online shopping platforms has transformed the shopping experience, leading to increased impulsive and unplanned purchases, also known as "purchasing gluttony." Using a quantitative approach and a descriptive analysis, this research investigates the impact of discounts and promotions on the inclination towards purchasing gluttony. The findings demonstrate that these strategies significantly influence consumers' tendency to engage in excessive buying. To foster loyalty and regular purchasing behavior, products should have a lasting impact on customers. However, the study reveals a limited awareness among Saudi society regarding the negative consequences of compulsive buying on the environment. Therefore, the study recommends educating consumers about sustainability and their role in promoting rational clothing consumption. It also suggests encouraging retailers and marketers to reduce the frequency of discounts throughout the year, thereby supporting environmental preservation initiatives in collaboration with the Chamber of Commerce. Future research should focus on sustainability and consumer purchasing behavior while shedding light on the adverse effects of compulsive buying on individuals, society, and the environment.
Keywords: Compulsive purchasing; opportunistic sales; discounts; environmental pollution